A high copper adhesion catheter material and preparation method thereof

By using high copper adhesive conduit materials and specific process treatment, the problem of copper powder agglomeration in the thermal conduit manufacturing process is solved, and the thermal conductivity and strength of the conduit is improved, making it suitable for automated production.

CN119772168APending Publication Date: 2025-04-08CHONGQING ZHIBO POWDER METALLURGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411991190.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The existing thermal conduits are prone to copper powder agglomeration during the manufacturing process, resulting in low thermal conductivity and insufficient porosity and connectivity.

Method used

A high-copper adhesive conduit material is adopted, including carbon powder, electrolytic copper powder, iron-molybdenum powder, adhesive, atomized iron powder and tungsten powder. Through temperature-pressure molding and multi-stage temperature zone sintering, a more favorable inner wall capillary structure layer is formed to avoid agglomeration.

Benefits of technology

It improves the thermal conductivity and strength of the conduit, extends the service life, and is suitable for automated production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005223684000000051
    Figure BDA0005223684000000051
  • Figure BDA0005223684000000061
    Figure BDA0005223684000000061
Patent Text Reader

Abstract

The present invention relates to the technical field of composite materials, and discloses a high-copper adhesiveness catheter material and a preparation method thereof, which is prepared by the following raw materials in parts by weight: 0.8-1.7 parts of carbon powder, 20-35 parts of electrolytic copper powder, 5-7 parts of iron-molybdenum powder, 5-15 parts of adhesive, 40-50 parts of atomized iron powder, and 0.5-1.8 parts of tungsten powder. The high-copper adhesiveness catheter material provided by the present invention adopts a large amount of relatively low-priced iron-molybdenum powder, atomized iron powder and carbon powder, which can save the amount of copper and has low cost; based on the iron-molybdenum powder, atomized iron powder and carbon powder, the added electrolytic copper powder contains multi-element copper, which can effectively fill the porosity in the catheter, so that the catheter produces a more favorable inner wall capillary structure layer, and also increases the catheter density and its heat conduction. At the same time, on this basis, the added adhesive can avoid the electrolytic copper powder from agglomerating during the manufacturing process, and improve the strength of the catheter.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of composite materials, and in particular to a catheter material with high copper adhesion and a preparation method thereof. Background Art

[0002] In recent years, with the rapid development of aerospace, electrical and electronic fields, especially the rapid development of semiconductor manufacturing and electronic packaging technology, the working efficiency of electronic and electrical components has been greatly improved. However, as the components are working quickly, the heat consumption is also increasing, and the working life and working stability of the components are also severely restricted. According to statistics, every time the working temperature of the CPU rises by 10°C, its life will be reduced by 50%; when the working temperature of the motor rises by 20°C, its failure rate will increase by 30%. Therefore, effectively conducting and processing this part of the heat consumption is crucial to ensure the working stability and life of the device.

[0003] The mainstream heat dissipation devices today include: cooling fans, heat sinks, heat dissipation modules and radiators. The core heat transfer component of heat sinks, heat dissipation modules and radiators is the heat pipe. The heat pipe consists of a metal tube and a capillary structure layer on the inner wall of the tube. The heat dissipation fluid is contained inside. When one end of the heat pipe is heated, the fluid absorbs heat and vaporizes to form high-temperature gas. The other end of the heat pipe condenses the high-temperature gas into liquid fluid due to the lower temperature. The liquid fluid returns to the heated end under the capillary force of the capillary structure layer. This process is repeated to form a continuous phase change heat transfer system.

[0004] The application of heat pipes is very extensive and is constantly expanding. At present, they are mainly used in the following aspects: (1) aerospace engineering, such as cooling and heat dissipation of electronic compartments and uniform temperature of spacecraft surfaces; (2) energy-saving engineering, such as waste heat recovery of various flue gases and air-conditioning exhaust; (3) heat dissipation of electronic devices, such as LEDs and computer components; (4) electrical systems, such as cooling of engines or motors; (5) mechanical processing, such as cooling of castings and cutting tools.

[0005] Copper has become the main metal for manufacturing heat pipes due to its excellent heat transfer characteristics and relatively low price. The capillary structure layer on the inner wall of the heat pipe is required to have a high porosity on the one hand to ensure sufficient heat source contact area; on the other hand, the pores inside the capillary structure material are required to be well connected and have a high capillary force to ensure that the liquid heat dissipation fluid or medium in certain devices can pass smoothly and quickly.

[0006] However, in the actual manufacturing process of the catheter, the catheter is usually manufactured by copper infiltration. In the copper infiltration process, since the porosity of the copper powder after sintering (the sintering temperature is 900-1050°C) is less than 55%, and the pore connectivity is less than 85%, agglomeration is likely to occur during copper infiltration, resulting in low thermal conductivity of the catheter. Therefore, a catheter material with high copper adhesion is needed to produce a more favorable inner wall capillary structure layer, avoid agglomeration, and improve the thermal conductivity of the catheter. Summary of the invention

[0007] The present invention aims to provide a catheter material with high copper adhesion and a preparation method thereof, which can produce a more favorable inner wall capillary structure layer, avoid agglomeration, and improve the heat conduction efficiency of the catheter.

[0008] In order to achieve the above object, the present invention adopts the following technical scheme:

[0009] 1) A high copper adhesion catheter material is prepared by including the following raw materials in parts by weight: 0.8-1.7 parts of carbon powder, 20-35 parts of electrolytic copper powder, 5-7 parts of iron-molybdenum powder, 5-15 parts of adhesive, 40-50 parts of atomized iron powder, and 0.5-1.8 parts of tungsten powder.

[0010] The high copper adhesion catheter material provided by the present invention adopts a large amount of relatively low-priced iron-molybdenum powder, atomized iron powder and carbon powder, which can save copper usage and has low cost; based on the iron-molybdenum powder, atomized iron powder and carbon powder, the added electrolytic copper powder contains multi-element copper, which can effectively fill the porosity in the catheter, so that the catheter produces a more favorable inner wall capillary structure layer, and also increases the catheter density and heat conduction. At the same time, on this basis, the added adhesive can avoid agglomeration of the electrolytic copper powder during the manufacturing process, thereby improving the strength of the catheter.

[0011] 2) A high copper adhesion catheter material according to 1), wherein:

[0012] The carbon powder is 0.8 parts, the electrolytic copper powder is 20 parts, the iron-molybdenum powder is 5 parts, the adhesive is 5 parts, the atomized iron powder is 40 parts and the tungsten powder is 0.5 parts.

[0013] 3) A high copper adhesion catheter material according to 1), wherein:

[0014] The carbon powder is 1.5 parts, the electrolytic copper powder is 30 parts, the iron-molybdenum powder is 6 parts, the adhesive is 10 parts, the atomized iron powder is 45 parts and the tungsten powder is 1 part.

[0015] 4) A high copper adhesion catheter material according to 1), wherein:

[0016] The carbon powder is 1.7 parts, the electrolytic copper powder is 35 parts, the iron-molybdenum powder is 7 parts, the adhesive is 15 parts, the atomized iron powder is 50 parts and the tungsten powder is 1.8 parts.

[0017] 5) A high copper adhesion catheter material according to 1), wherein:

[0018] The mass ratio of iron to molybdenum in the iron-molybdenum powder is (3-6):1.

[0019] 6) A high copper adhesion catheter material according to 1), wherein:

[0020] The electrolytic copper powder includes copper and chromium, and the mass ratio of copper to chromium is (13-16):1.

[0021] 7) A method for preparing a high copper adhesion catheter material, which is applied to the high copper adhesion catheter material described in 1) to 6) above, comprising the following steps:

[0022] Step 1: Mix carbon powder, iron-molybdenum powder and atomized iron powder in parts by weight to obtain a mixture, and perform warm pressing on the mixture to obtain a base blank. Meanwhile, perform warm pressing on the electrolytic copper powder to obtain a copper blank.

[0023] Step 2: Use the copper billet to perform copper infiltration and sintering on the base billet. During the sintering process, add a matching adhesive in weight to the base billet to obtain a copper infiltrated steel billet; perform multi-stage temperature zone sintering and vacuum oil impregnation on the copper infiltrated steel billet in sequence to obtain a copper infiltrated catheter material.

[0024] When the copper billet is used to copper-infiltrate and sinter the base billet, an adhesive is used to control the copper infiltration amount, thereby avoiding agglomeration during the copper infiltration process, thereby obtaining a copper-infiltrated steel billet. On the basis of the copper-infiltrated steel billet, multi-stage temperature zone sintering and vacuum oil immersion can effectively remove air in the pores of the copper-infiltrated conduit material, and grease and adhesive are simultaneously pressed into the copper-infiltrated conduit material to fill the pores, thereby improving the high density and high strength of the copper-infiltrated conduit material and extending the service life of the copper-infiltrated conduit material.

[0025] 8) A method for preparing a catheter material with high copper adhesion according to 7), wherein:

[0026] The pressure of the mixture during warm pressing is 241-358KN, the temperature is 25-36°C, and the heat preservation and pressure holding time is 2-8min;

[0027] The pressure during warm pressing of the electrolytic copper powder is 148-198 KN, the temperature is 20-30° C., and the heat preservation and pressure holding time is 3-7 minutes.

[0028] The present invention performs warm pressing on the mixed material and the electrolytic copper powder respectively. Under the condition of heat preservation and pressure preservation, the compactness and wear resistance of the mixed material and the electrolytic copper powder can be improved, the chemical properties of the base blank formed by the warm pressing of the mixed material are stable, the chemical properties of the copper blank formed by the warm pressing of the electrolytic copper powder are stable, and the copper infiltrated conduit material has high strength.

[0029] 9) A method for preparing a catheter material with high copper adhesion according to 7), wherein:

[0030] The copper infiltration sintering temperature is 1100°C±5°C and the time is 12-15 minutes.

[0031] 10) A method for preparing a catheter material with high copper adhesion according to 7), wherein:

[0032] The vacuum oil immersion process is performed at a pressure of 0.4-0.8 MPa and a time of 5-10 min.

[0033] Compared with the prior art, the present invention also has the following technical effects:

[0034] Compared with the prior art, the present invention has simplified preparation steps, precise finished products, and is conducive to large-scale automated production. The catheter material manufactured by the present method is based on iron-molybdenum powder, atomized iron powder and carbon powder, and the added electrolytic copper powder contains multi-element copper, which can effectively fill the porosity in the catheter, so that the catheter produces a more favorable inner wall capillary structure layer, increases the permeability of copper infiltration in the catheter material, and prevents agglomeration during the copper infiltration process through the adhesive, thereby improving the thermal conductivity and heat removal power of the catheter.

[0035] Add higher alloys and use copper infiltration technology for displacement engines to improve the wear resistance of the conduit, matrix density, strength and thermal conductivity. Use anti-segregation mixing, stack and sinter the formed blank with the copper blank, and the copper is evenly melted and infiltrated into the matrix to obtain a dense conduit. DETAILED DESCRIPTION

[0036] The following is further described in detail through specific implementation methods:

[0037] Example 1

[0038] A high copper adhesion catheter material, comprising 0.8 parts of carbon powder, 20 parts of electrolytic copper powder, 5 parts of iron-molybdenum powder, 5 parts of adhesive, 40 parts of atomized iron powder and 0.5 parts of tungsten powder; wherein the mass ratio of iron to molybdenum in the iron-molybdenum powder is (3-6):1; the electrolytic copper powder comprises copper and chromium, and the mass ratio of copper to chromium is (13-16):1.

[0039] Example 2

[0040] A high copper adhesion catheter material, comprising 1.5 parts of carbon powder, 30 parts of electrolytic copper powder, 6 parts of iron-molybdenum powder, 10 parts of adhesive, 45 parts of atomized iron powder and 1 part of tungsten powder; wherein the mass ratio of iron to molybdenum in the iron-molybdenum powder is (3-6):1; the electrolytic copper powder comprises copper and chromium, and the mass ratio of copper to chromium is (13-16):1.

[0041] Example 3

[0042] A high copper adhesion catheter material, comprising 1.7 parts of carbon powder, 35 parts of electrolytic copper powder, 7 parts of iron-molybdenum powder, 15 parts of adhesive, 50 parts of atomized iron powder and 1.8 parts of tungsten powder; wherein the mass ratio of iron to molybdenum in the iron-molybdenum powder is (3-6):1; the electrolytic copper powder comprises copper and chromium, and the mass ratio of copper to chromium is (13-16):1.

[0043] The method for preparing a high copper adhesion catheter material in the above-mentioned embodiments 1 to 3 comprises the following steps:

[0044] Step 1: Mix carbon powder, iron-molybdenum powder and atomized iron powder in parts by weight to obtain a mixture, and perform warm pressing on the mixture to obtain a base blank. At the same time, perform warm pressing on the electrolytic copper powder to obtain a copper blank; wherein the pressure during warm pressing of the mixture is 300KN, the temperature is 30°C, and the heat preservation and pressure holding time is 6min;

[0045] The pressure during warm pressing of the electrolytic copper powder is 158 KN, the temperature is 25° C., and the heat preservation and pressure holding time is 5 minutes.

[0046] Step 2: Use the copper billet to perform copper infiltration and sintering on the base billet, the copper infiltration and sintering temperature is 1100°C ± 5°C, the time is 10min, and during the sintering process, add a matching adhesive in weight to the base billet to obtain a copper infiltrated steel billet; perform multi-stage temperature zone sintering and vacuum oil immersion on the copper infiltrated steel billet in sequence, the vacuum oil immersion pressure is 0.5Mpa, and the time is 7min to obtain a copper infiltrated catheter material.

[0047] Among them, the multi-stage temperature zone sintering is preferably three-stage sintering, and the temperatures of each stage sintering are preferably 540°C, 680°C and 958°C, respectively. In Examples 1-3, each stage of the multi-stage temperature zone sintering lasts 8-12 minutes, preferably 10 minutes. Push rod sintering is adopted, and the copper-infiltrated billet is automatically pushed into the furnace in a cycle and sintered in different temperature zones. The use of multi-stage temperature zone sintering can prevent oxidation, deformation, decarburization and other phenomena of the sintered billet, so that the different components in the material are fully diffused to achieve good mechanical properties.

[0048] Comparative Example 1

[0049] Compared with Example 1, the difference is that a catheter material is prepared by including the following raw materials in parts by weight: 50 parts of carbon powder and 50 parts of electrolytic copper powder. The preparation method uses carbon powder as a base blank and electrolytic copper powder as a copper blank, and does not add an adhesive during the preparation process.

[0050] Comparative Example 2

[0051] Compared with Example 1, the difference is that a catheter material is prepared by including the following raw materials in parts by weight: 50 parts of iron-molybdenum powder and 50 parts of electrolytic copper powder. The preparation method uses carbon powder as the base blank and electrolytic copper powder as the copper blank, and no adhesive is added during the preparation process.

[0052] Comparative Example 3

[0053] Compared with Example 1, the difference is that a catheter material is prepared by including the following raw materials in parts by weight: 50 parts of atomized iron powder and 50 parts of electrolytic copper powder. The preparation method uses carbon powder as the base blank and electrolytic copper powder as the copper blank, and no adhesive is added during the preparation process.

[0054] Comparative Example 4

[0055] The same as Example 1, except that no adhesive is added in the preparation method.

[0056] Effect verification:

[0057] The catheter materials prepared in Examples 1-3 and Comparative Examples 1-4 were numbered 1-7, and the compressive strength tests and corrosion status comparisons of No. 1-7 were performed, as shown in Table 1.

[0058]

[0059]

[0060] As shown in Table 1, the compressive strength of No. 1-3 is higher than that of No. 4-7. It can be seen that the catheter material prepared in Example 1-3 is based on iron-molybdenum powder, atomized iron powder and carbon powder, and the added electrolytic copper powder contains multi-element copper, which can effectively fill the porosity in the catheter, so that the catheter produces a more favorable inner wall capillary structure layer, and also increases the density of the catheter and its heat conduction. At the same time, on this basis, the added adhesive can prevent the electrolytic copper powder from agglomerating during the manufacturing process and improve the strength of the catheter.

[0061] In addition, in terms of corrosion conditions, No. 1-3 is much better than No. 4-7, and the corrosion condition of No. 7 is better than No. 4-6, and bonding occurs. That is to say, without adding an adhesive, the added electrolytic copper powder contains multi-element copper based on iron-molybdenum powder, atomized iron powder and carbon powder, which can effectively fill the porosity in the catheter, making the catheter dense and corrosion-resistant. Similarly, an adhesive is added to No. 1-3. Therefore, during the preparation process of the catheter, the agglomeration of copper infiltration is effectively prevented, thereby further concentrating the density of the catheter, making the corrosion resistance of No. 1-3 higher than that of No. 7.

[0062] The above are only embodiments of the present invention, and the common knowledge such as the known specific technical solutions and / or characteristics in the solution are not described in detail here. It should be pointed out that for those skilled in the art, several modifications and improvements can be made without departing from the technical solution of the present invention, which should also be regarded as the protection scope of the present invention, and these will not affect the effect of the implementation of the present invention and the practicality of the patent. The scope of protection required by this application shall be based on the content of its claims, and the specific implementation methods and other records in the specification can be used to interpret the content of the claims.

Claims

1. A high copper adhesion catheter material, characterized in that: The invention is prepared by including the following raw materials in parts by weight: 0.8-1.7 parts of carbon powder, 20-35 parts of electrolytic copper powder, 5-7 parts of iron-molybdenum powder, 5-15 parts of adhesive, 40-50 parts of atomized iron powder and 0.5-1.8 parts of tungsten powder.

2. The high copper adhesion catheter material according to claim 1, characterized in that: The carbon powder is 0.8 parts, the electrolytic copper powder is 20 parts, the iron-molybdenum powder is 5 parts, the adhesive is 5 parts, the atomized iron powder is 40 parts and the tungsten powder is 0.5 parts.

3. The high copper adhesion catheter material according to claim 1, characterized in that: The carbon powder is 1.5 parts, the electrolytic copper powder is 30 parts, the iron-molybdenum powder is 6 parts, the adhesive is 10 parts, the atomized iron powder is 45 parts and the tungsten powder is 1 part.

4. The high copper adhesion catheter material according to claim 3, characterized in that: The carbon powder is 1.7 parts, the electrolytic copper powder is 35 parts, the iron-molybdenum powder is 7 parts, the adhesive is 15 parts, the atomized iron powder is 50 parts and the tungsten powder is 1.8 parts.

5. The high copper adhesion catheter material according to claim 1, characterized in that: The mass ratio of iron to molybdenum in the iron-molybdenum powder is (3-6):

1.

6. The high copper adhesion catheter material according to claim 1, characterized in that: The electrolytic copper powder includes copper and chromium, and the mass ratio of copper to chromium is (13-16):

1.

7. A high copper adhesion catheter material and a preparation method thereof, characterized in that: A high copper adhesion catheter material applied to any one of claims 1 to 6, comprising the following steps: Step 1: Mix carbon powder, iron-molybdenum powder and atomized iron powder in parts by weight to obtain a mixture, and perform warm pressing on the mixture to obtain a base blank. Meanwhile, perform warm pressing on the electrolytic copper powder to obtain a copper blank. Step 2: Use the copper billet to perform copper infiltration and sintering on the base billet. During the sintering process, add a matching adhesive in weight to the base billet to obtain a copper infiltrated steel billet; perform multi-stage temperature zone sintering and vacuum oil impregnation on the copper infiltrated steel billet in sequence to obtain a copper infiltrated catheter material.

8. The high copper adhesion catheter material and the preparation method thereof according to claim 7, characterized in that: The pressure of the mixture during warm pressing is 241-358KN, the temperature is 25-36°C, and the heat preservation and pressure holding time is 2-8min; The pressure during warm pressing of the electrolytic copper powder is 148-198 KN, the temperature is 20-30° C., and the heat preservation and pressure holding time is 3-7 minutes.

9. The high copper adhesion catheter material and the preparation method thereof according to claim 7, characterized in that: The copper infiltration sintering temperature is 1100°C±5°C and the time is 12-15 minutes.

10. The high copper adhesion catheter material and the preparation method thereof according to claim 7, characterized in that: The vacuum oil immersion process is performed at a pressure of 0.4-0.8 MPa and a time of 5-10 min.